y′′′−2y′′−y′+2y=e4x
variation of paramaters
Let us solve the differential equation "y'''\u22122y''\u2212y'+2y=e^{4x}" using the method of variation of paramaters. For this, firstly solve the characteristic equation "k^3-2k^2-k+2=0" of "y'''\u22122y''\u2212y'+2y=0". This characteristic eqution is equivalent to "k^2(k-2)-(k-2)=0" which is equivalent to "(k^2-1)(k-2)=0". Therefore, "k_1=1,k_2=-1,k_3=2." According to the method of variation of paramaters, the solution of "y'''\u22122y''\u2212y'+2y=e^{4x}" is
"y(x)=C_1(x)e^x+C_2(x)e^{-x}+C_3(x)e^{2x}."
Then we have the following system:
"\\begin{cases}\nC_1'(x)e^x+C_2'(x)e^{-x}+C_3'(x)e^{2x}=0\\\\\nC_1'(x)e^x-C_2'(x)e^{-x}+2C_3'(x)e^{2x}=0\\\\\nC_1'(x)e^x+C_2'(x)e^{-x}+4C_3'(x)e^{2x}=e^{4x}\n\\end{cases}"
which is equivalent to
"\\begin{cases}\nC_1'(x)e^x+C_2'(x)e^{-x}+C_3'(x)e^{2x}=0\\\\\n2C_1'(x)e^x+3C_3'(x)e^{2x}=0\\\\\n3C_3'(x)e^{2x}=e^{4x}\n\\end{cases}"
"\\begin{cases}\nC_2'(x)=-C_1'(x)e^{2x}-C_3'(x)e^{3x}\\\\\nC_1'(x)=-\\frac{3}{2}C_3'(x)e^{x}\\\\\nC_3'(x)=\\frac{1}{3}e^{2x}\n\\end{cases}"
"\\begin{cases}\nC_2'(x)=\\frac{1}{2}e^{5x}-\\frac{1}{3}e^{5x}\\\\\nC_1'(x)=-\\frac{1}{2}e^{3x}\\\\\nC_3'(x)=\\frac{1}{3}e^{2x}\n\\end{cases}"
"\\begin{cases}\nC_2'(x)=\\frac{1}{6}e^{5x}\\\\\nC_1'(x)=-\\frac{1}{2}e^{3x}\\\\\nC_3'(x)=\\frac{1}{3}e^{2x}\n\\end{cases}"
"\\begin{cases}\nC_2(x)=\\frac{1}{30}e^{5x}+C_2\\\\\nC_1(x)=-\\frac{1}{6}e^{3x}+C_1\\\\\nC_3(x)=\\frac{1}{6}e^{2x}+C_3\n\\end{cases}"
Therefore, the solution is the following:
"y(x)=(-\\frac{1}{6}e^{3x}+C_1)e^x+(\\frac{1}{30}e^{5x}+C_2)e^{-x}+(\\frac{1}{6}e^{2x}+C_3)e^{2x}="
"=C_1e^x+C_2e^{-x}+C_3e^{2x}+\\frac{1}{30}e^{4x}."
Comments
Leave a comment